The relationship between caffeine consumption and colon cancer prevalence in a nationally representative population - Qu, Yuhua; Cheng, Yulu; Chen, Fengming (Frontiers in Nutrition, 2024)
Aims This study examines the correlation between caffeine consumption and the prevalence of colon cancer. Methods Utilizing data from the National Health and Nutrition Examination Survey (NHANES) for the years 2001 to 2014, we applied weighted logistic regression to evaluate the association between caffeine consumption and the prevalence of colon cancer. This analysis accounted for variables including age, gender, race, education, poverty income ratio, smoking status, alcohol consumption, and diabetes. The findings were expressed as weighted odds ratios (ORs) with accompanying 95% confidence intervals (CIs). The restricted cubic spline analysis was performed to exam the dose-dependent relationship. Results The study included 27,637 participants, of which 144 were diagnosed with colon cancer and 27,493 served as controls. Individuals in the highest quartile (Q4) of caffeine consumption (Q4) displayed a significantly increased risk of colon cancer compared to those in the lowest quartile (Q1), with a weighted OR of 2.00 (95% CI: 1.11-3.59; P = 0.022). Additionally, restricted cubic spline analysis indicated a significant correlation between higher caffeine intake and increased colon cancer risk, with an overall association P-value of 0.007. Conclusion These findings suggest a potential relationship between higher levels of caffeine consumption and an increased risk of colon cancer. The dose-response relationship suggests a notable correlation at higher caffeine intake levels. Further investigations are warranted to confirm these results and elucidate potential underlying mechanisms.